Gambaran Pengetahuan Kebersihan Diri Dalam Pencegahan Penularan Covid-19 Pada Masyarakat Argomulyo Salatiga - David Nakka Gasong; Dennys Christovel Dese; Allivia Nolasari Hidayat (Jurnal Keperawatan Muhammadiyah, 2022)
The increase in virus covid-19 happened so fast in Indonesia in 2020 resulted in the community to experience a change in behavior as a society should pay attention to the protocols of health that has already been applied as well as maintain personal hygiene. But not yet fully community care about the cleanliness of her. The purpose of this research is to know the description of the knowledge society in Kecamatan Argomulyo Village Ledok Salatiga related to personal hygiene in the prevention of transmission of the virus covid-19. Methods in this study using the technique of observational and survey a descriptive analytic. This study will illustrate how the knowledge society in Kecamatan Argomulyo Village Ledok Salatiga related to personal hygiene in the prevention of transmission of the virus covid-19. The results in this study indicate that as many as 57% of the People Argamas Eastern RW 09 Salatiga already understand and as much as 43% have yet to understand the related knowledge about covid-19. Conclusion in this research that the community Argamas Eastern RW 09 has a good level of knowledge but there are some things that need more attention that is about the personal hygiene that must be enhanced in order to prevent the occurrence of transmission of the virus covid-19.